An Effective Open ERP System for Automation in Financial Reporting for SMEs based on Service Oriented Architecture - Saputra, Muhardi; Fadlila, Rafa Fadlila (Society of Visual Informatics, 2023)
Small-Medium Enterprises (SMEs) are currently in high demand and highly developed in many countries. However, several SMEs still do not yet have an information system to support their business processes. This causes the absence of a system that helps integrate data from each process and sector in SMEs. All data exchanges and transaction report generation are done manually and recorded using physical documents that reduce effectiveness and increase costs. This research uses the accounting module in Open ERP or Odoo Version 11.0 software and Service Oriented Architecture (SOA) methods to design ERP systems for general types of SMEs in the finance sector, specifically on the sales and purchase process. So the solution for recording financial transactions and making financial reports for SMEs is to design an ERP system based on Open Source using the Service Oriented Architecture methodology, namely Smart SMEs, by implementing the Automatic Reporting feature to create best practices on an integrated system, especially in recording transactions in the sales and purchase processes so that financial reports can be generated automatically and are real-time. The result of this research is the design of ERP systems in the finance section connected occurs especially in the financial recording of the purchase of goods, the sale of goods, and the creation of financial statements automatically. This system can help the finance sector record transactions and make automatic financial reports that can be generated in real-time.